Synergistic Hf-rGO Reinforcement in Copper: A Pathway to Electrically Functional, Wear-Resistant Hybrid Composites - Macit, Cevher Kursat; Aksakal, Bunyamin; Ayik, Merve; Gurgenc, Turan; Er, Yusuf (Mdpi, 2026)
Copper (Cu) is widely used in electrical and thermal management systems; however, its low hardness and limited dry sliding wear resistance reduce long-term reliability in friction-loaded conductive components. In this study, Cu-Hf and Cu-Hf-rGO hybrid composites were fabricated by powder metallurgy using 1.0-5.0 wt.% Hf and 1.0-2.0 wt.% reduced graphene oxide (rGO). The microstructure and phase evolution were characterized by SEM/EDS and XRD. Electrical conductivity and hardness were measured, while tribological performance was evaluated by dry sliding wear tests based on mass loss. Post-wear surface characteristics were analyzed by AFM and LFM to assess nanoscale topography and frictional behavior. The hybrid composites exhibited composition-dependent multifunctional enhancements. Electrical conductivity increased from approximately 3.0 x 10(6) S/m (similar to 5.2% IACS) for pristine Cu to about 2.0 & times; 10(7) S/m (similar to 34.5% IACS) for the composite reinforced with 3.0 wt.% Hf and 2.0 wt.% rGO, indicating an optimum Hf-rGO combination that preserves continuous conductive pathways. Hardness increased from 60 +/- 3 HV0.30 to 159 +/- 12 HV0.30 for the composite containing 5.0 wt.% Hf and 2.0 wt.% rGO, demonstrating the dominant contribution of Hf to matrix strengthening and load-bearing capacity. The mass loss after 1000 m of sliding distance decreased from about 0.12 g for Cu to approximately 0.01 g for the 5.0 wt.% Hf-2.0 wt.% rGO hybrid composite, consistent with the concurrent increase in hardness and reduction in frictional shear during sliding. Nanoscale surface analyses revealed reduced surface roughness and frictional response, supporting the formation of a smoother and lower-friction sliding interface in rGO-containing composites. Overall, Hf enhanced load-bearing capacity through matrix strengthening, while rGO contributed to stabilizing conductive pathways and solid lubrication.
Keywords: copper matrix composite; graphene oxide (rGO); hafnium; tribology; powder metallurgy